1999
DOI: 10.1095/biolreprod61.4.1042
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl Phosphatidylinositol-Anchored Ceruloplasmin Is Expressed by Rat Sertoli Cells and Is Concentrated in Detergent-Insoluble Membrane Fractions1

Abstract: The copper-binding protein, ceruloplasmin, is both a serum component and a secretory product of Sertoli cells. Studies on serum ceruloplasmin have demonstrated it to be a ferroxidase that is essential for iron transport throughout the body. We report here that a glycosyl phosphatidylinositol (GPI)-anchored form of ceruloplasmin is expressed by Sertoli cells. Sertoli cell GPI-anchored proteins were selectively released by phosphatidylinositol-specific phospholipase C and were analyzed by Western blotting. A 135… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…These metabolic studies accurately reflect newly synthesized holoceruloplasmin, because previous studies have shown that no copper is incorporated into previously synthesized apoceruloplasmin (23). The observation that GPI-linked ceruloplasmin also incorporates copper is consistent with studies demonstrating oxidase activity of this isoform in the rat (7,9). Interestingly, recent studies revealed that GPI-anchored proteins are sorted from other proteins within the ER early in the secretory pathway (32).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These metabolic studies accurately reflect newly synthesized holoceruloplasmin, because previous studies have shown that no copper is incorporated into previously synthesized apoceruloplasmin (23). The observation that GPI-linked ceruloplasmin also incorporates copper is consistent with studies demonstrating oxidase activity of this isoform in the rat (7,9). Interestingly, recent studies revealed that GPI-anchored proteins are sorted from other proteins within the ER early in the secretory pathway (32).…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with this concept, in patients with Wilson disease, the absence or dysfunction of a copper-transporting ATPase abrogates copper transfer into the secretory pathway, resulting in marked diminution in the serum concentration of ceruloplasmin (4). Extrahepatic synthesis of human ceruloplasmin has been detected in several tissues, including the retina and brain (5,6), and recent studies in rodents suggest that in brain and testis ceruloplasmin is synthesized as a glycosylphosphatidylinositol (GPI) 1 -anchored form via alternative RNA splicing (7)(8)(9)(10).…”
mentioning
confidence: 88%
“…In particular, a membrane-bound glycosylphosphatidylinositol (GPI)-anchored form of CP (GPI-CP) localized at the surface of mammalian astrocytes [28], rat leptomeningeal cells [29], and Sertoli cells [30] was reported. However, despite the detection of CP mRNA in immune cells [31,32], the characterization of the specific molecular isoform (s) expressed by huPBL has never been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to transferrin and TfR1, other proteins involved in iron transport, such as DMT1 and glycosyl phosphatidylinositol-anchored ceruloplasmin (11,13,42,46), and iron storage, such as cytosolic and mitochondrial ferritin, were found in the testis. DMT1 is suggested to be expressed in a stage-dependent manner in the elongating spermatids and in the cytosol and nuclei of SC of adult rat testis, where it may play a role in iron uptake (13), but the source of this iron has not been identified so far.…”
mentioning
confidence: 99%
“…The mRNA analysis of cytosolic ferritin showed that transcript levels of the ferritin H-subunit were significantly higher than L-subunits, and in the cell types analyzed the highest expression was found in PTM and SC, followed by the early spermatocytes and decreasing as spermatocytes mature (Table 1; also see http://public.wsu.edu/ Ïłgriswold/microarray/). Cellular localization of glycosyl phosphatidylinositol-anchored ceruloplasmin has never been determined (11,46).…”
mentioning
confidence: 99%